The political guarantees of the continuity of the federal state - Iraq is a model A comparative study - األسخاذ امىساغد امدكخِر شؤرش حسي غىر, (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
The federal state is based on some of the basic principles and foundations through them the regions contribute effectively to the institutions of the federal government and the success or collapse of the federal state, based on the defending of these principles and foundations through the establishment of various guarantees, including legal, judicial and political. In this study, we attempted to study the entitled "Political Guarantees for the Continuation of the Federal State - Iraq as a Model", which has a greater role in this area than other guarantees. And dealt with in two sections the first section we devoted to the study the foundations of the federal state, including the federal government's priority to the governments of the regions, the recognition of the authority of the self-report of the regions, and finally the distribution of sovereign competencies between federal and regional levels of government, the second part was devoted to the study of realistic guarantees for the success and sustainability of the federal union, including the building of the state. Federalism on the basis of choice and free will, and the foundations and principles of democracy, and finally the effective participation of the regions in the federal government. We have reached a set of results, the most important of which is that the Iraqi federal experience will not move towards continuity and stability because it emerged mainly from the needs of the interim or convictions of circumstantial one side or that, as well as the absence of democratic bases and principles fully governing institutions in the federal Iraq, which will lead to disintegration and collapse. As we have reached some proposals, among them, the proposal to amend the Constitution in a way that includes an explicit text on this union between the federal units with freewill and choice. As well as the adoption of the Constitution in one of its basic articles against the bodies and individuals to resist cases of violation of democratic principles set out in it, and the organization of the Council of the Union in terms of composition and jurisdiction of the text of the Constitution in such a way as to ensure the initial achievement of autonomy and participation of the Territories, and ensure the contribution of the Regions to any amendment to the federal constitution either directly Or indirectly, so that the federal government will not be able to make the amendment without the consent of the regions.